2015
DOI: 10.5603/fhc.a2014.0030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of monosodium glutamate treatment on calretinin-immunoreactive neurons in hippocampus of postnatal rats

Abstract: Introduction. Calretinin (CR) is a protein, which is present in GABAergic neurons and belongs to the calciumbinding proteins family. It may reduce the excitotoxicity phenomenon through its Ca 2+ buffering properties. This phenomenon is due to the increase of calcium ions levels caused by the excess of glutamate -the main excitatory neurotransmitter. The aim of the study was to investigate alterations of calretinin-immunoreactivity in neurons of hippocampal CA1 region and dentate gyrus with hilus in 10 day-old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 32 publications
2
11
0
1
Order By: Relevance
“…These degenerative effects greatly affected memory because they disrupted the normal flow of information from the dentate gyrus to CA3 through mossy fibers, and also may have affected the flow of information from CA3 via the Schaffer's fibers to CA1 [26]. Our findings were in agreement with Rycerz et al [25], who found that administration of MSG to rats in postnatal week revealed loss of 11.5% of pyramidal neurons in the hippocampus. On the other hand, MSG significantly increased astrogliosis, which was evidenced by increased GFAP expression ( Figure 6), a hallmark of increased astrocyte activity as a result of injury to the central nervous system [52].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These degenerative effects greatly affected memory because they disrupted the normal flow of information from the dentate gyrus to CA3 through mossy fibers, and also may have affected the flow of information from CA3 via the Schaffer's fibers to CA1 [26]. Our findings were in agreement with Rycerz et al [25], who found that administration of MSG to rats in postnatal week revealed loss of 11.5% of pyramidal neurons in the hippocampus. On the other hand, MSG significantly increased astrogliosis, which was evidenced by increased GFAP expression ( Figure 6), a hallmark of increased astrocyte activity as a result of injury to the central nervous system [52].…”
Section: Discussionsupporting
confidence: 91%
“…Beside its antioxidant effect, Allium sativum reduces cell damage through an anti-inflammatory property and decreases mitochondrial disorders occurring in different diseases [59]. Furthermore, our results indicated that the expression of calretinin protein was increased in the brain tissue of the MSG-treated group, which is a neuroprotective protein that regulates calcium homeostasis by buffering excess calcium in cases of glutamate-induced excititoxicity [25]. Treatment with Allium sativum powder significantly reduced the expression of calretinin, as it reduced MSG-induced excitotoxicity.…”
Section: Discussionmentioning
confidence: 58%
“…With acute administration of METH, there was an unexpected increase in the numbers of neurons immunoreactive for calretinin in the medial PFC (Cg1, PrL and IL) and NAc (core and shell) that was statistically significant. Calcium binding proteins are responsible for decreasing excessive calcium ions found within neurons, and transient increases in calbindin or calretinin expression have previously been reported following cytotoxin administration (Henzi et al, 2009 ; Huang et al, 1995 ; Rycerz et al, 2014 ). As calretinin is a calcium binding protein, it is plausible that the reported increase in calretinin immunoreactivity may reflect increased intensity or expression of the calretinin protein within calretinin-expressing interneurons.…”
Section: Discussionmentioning
confidence: 99%
“…Calretinin is expressed in hilar mossy cells and in widely distributed subsets of GABAergic interneurons in the normal mouse hippocampus [ 48 ]. Calretinin maintains appropriate calcium ion concentration in cells and participates in the modulation of neuronal activity and synaptic plasticity [ 49 ]. Knockout mice lacking calretinin show no alteration in basal synaptic transmission but impaired LTP in the dentate gyrus [ 48 ].…”
Section: Discussionmentioning
confidence: 99%